Tinjauan Yuridis Eksploitasi Manusia Dalam Fenomena Mandi Lumpur - Puspitasari, Syalaisha Amani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Very massive technological development does not always bring positive effects but also brings negative effects. The development of creativity does not lead to a new social phenomenon, namely online begging. This phenomenon was later exacerbated by the alleged human exploitation of the process. So it elicits responses from various circles. Even the Ministry of Social Affairs issued Circular No. 2 of 2023 on the Control of Exploitation Activities and/or Begging Activities that Utilize the Elderly, Children, Disabled People, and/or Other Vulnerable Groups so that such actions do not proliferate. However, in fact, the circular was not effective enough to answer the problem. This study was conducted using a normative juridical method through a legislative approach and a case approach